2021
DOI: 10.1016/j.amsu.2021.102903
|View full text |Cite
|
Sign up to set email alerts
|

Low back pain and its related risk factors in health care providers at hospitals: A systematic review

Abstract: Background Health care personnel are exposed to ergonomic hazards, musculoskeletal disorders, and other work-related injuries. Low back pain is the most common musculoskeletal disorder. The aim of this study was to determine the prevalence of low back pain and the risk factors in health care personnel at the hospital in a form of a systematic review and meta-analysis. Methods In this systematic review and meta-analysis, the articles published in international electronic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0
9

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 26 publications
0
18
0
9
Order By: Relevance
“…The relationship between gender and low back pain suggests a higher occurrence in females. A systematic review on low back pain among health care workers described a significant association with female gender and low back pain [9] which was also noted in a smaller study amongst health workers in Nigeria [10]. Females are more prone to LBP than males as a result of the anatomical, physiological and structural factors as well as the fact that mechanical disadvantage, sprain and strain, are more common in women than men [11].…”
Section: Discussionmentioning
confidence: 78%
“…The relationship between gender and low back pain suggests a higher occurrence in females. A systematic review on low back pain among health care workers described a significant association with female gender and low back pain [9] which was also noted in a smaller study amongst health workers in Nigeria [10]. Females are more prone to LBP than males as a result of the anatomical, physiological and structural factors as well as the fact that mechanical disadvantage, sprain and strain, are more common in women than men [11].…”
Section: Discussionmentioning
confidence: 78%
“…For instance, a study conducted in New Zealand showed that unskilled workers were over two times more likely than their skilled counterparts (managers and professionals) to lift weights at least 25% of their working time (19). Additionally, MSDs in hands were found to be common among manual laborers (36,37), while back pain was frequently reported by drivers, handlers of heavy objects, and nurses and other patient-care workers (38)(39)(40).…”
Section: Discussionmentioning
confidence: 99%
“…There is a dearth of studies on WRIs among HCWs in Saudi Arabia [17][18][19][20]. Therefore, this study aims to assess WRIs and their impact on HCWs in Jeddah, Saudi Arabia.…”
Section: Introductionmentioning
confidence: 99%